Die Mathematisierung der Natur als intentionalhistorisches Problem In Husserls Krisis-Schrift - Dojan, Thomas (B@belonline, 2020)
This article is a contribution from the point of view of Edmund Husserl’s phenomenology to genetic philosophical studies of science as a collective historical and cultural achievement, but also as an undertaking to reach objective knowledge with absolute and timeless validity. In the Crisis of the European Sciences (1936), Edmund Husserl aims at developing a historical understanding of the motivations that gave rise to naturalism as an interpretation of reality to be mathematical in essence, thereby shedding light on how it is possible and what it means to assume the naturalistic attitude. This article goes back over Husserl’s analyses in the Crisis in three major sections: (i) by tracing historical meditations in the phenomenology of Edmund Husserl at large (the historical essence of consciousness); (ii) by presenting and interpreting Husserl’s intentional history of natural science in §9 of the Crisis (two of the central components of natural scientific practice – the idea of ‘universal causality’ and the idea of ‘ideality’ – can thus be traced back to pre-scientific forms manifesting in the life world); and (iii) by renewing Husserl’s self-reflections on the contemporary philosophical situation as they relate to our own times (the critique of the naturalization of consciousness).